2022
DOI: 10.1002/jcla.24592
|View full text |Cite
|
Sign up to set email alerts
|

The etiological roles of miRNAs, lncRNAs, and circRNAs in neuropathic pain: A narrative review

Abstract: Background Non‐coding RNAs (ncRNAs) are involved in neuropathic pain development. Herein, we systematically searched for neuropathic pain‐related ncRNAs expression changes, including microRNAs (miRNAs), long non‐coding RNAs (lncRNAs), and circular non‐coding RNAs (circRNAs). Methods We searched two databases, PubMed and GeenMedical, for relevant studies. Results Peripheral nerve injury or noxious stimuli can induce extensive changes in the expression of ncRNAs. For example, higher serum miR‐132‐3p, ‐146b‐5p, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 157 publications
0
9
0
Order By: Relevance
“…Consistent with this, long noncoding kcna2 antisense RNA silenced KCNA2 and contributed to NP in rats via reducing the voltage-gated potassium current and increasing DRG excitability [61]. In addition, several studies have linked the epigenetic repression of KCNA2 with the development of NP [62][63][64][65][66][67]. Based on the above, K channels could be an appropriate target for pain therapy in specific individuals.…”
Section: Kcna1 and Kcna2mentioning
confidence: 61%
“…Consistent with this, long noncoding kcna2 antisense RNA silenced KCNA2 and contributed to NP in rats via reducing the voltage-gated potassium current and increasing DRG excitability [61]. In addition, several studies have linked the epigenetic repression of KCNA2 with the development of NP [62][63][64][65][66][67]. Based on the above, K channels could be an appropriate target for pain therapy in specific individuals.…”
Section: Kcna1 and Kcna2mentioning
confidence: 61%
“…Microarray and deep-sequencing analyses revealed that nerve injury or noxious stimuli could induce broad changes in miRNA expression in serum or along the pain processing pathways. Dysregulated miRNAs contribute to neuropathic pain via neuroinflammation, autophagy, abnormal ion channel expression, regulating pain-related mediators, protein kinases, structural proteins, neurotransmission excitatory–inhibitory imbalances, or exosome miRNA-mediated neuron–glia communication [ 15 ]. There are several studies reporting changes in miRNA expression in patients with chronic pain, such as miR-146a, let-7a, miR-145, miR-550a, miR-132 and miR-3613 [ 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes can lead to the abnormal discharge of neurons and subsequently result in pain. 84 Consequently, ion channels play a pivotal role in determining neuronal excitability, and they might be subject to miRNA regulation under painful conditions. It is worth noting that voltage-gated channels, implicated in the pain pathway, have become the primary focus of interventions for treating neuropathic pain.…”
Section: Regulation Of Neuronal Ion Channelsmentioning
confidence: 99%